Cyber Security and Impact on Computer Crimes - Pantea, Andrei (Acta Universitatis Danubius. Juridica, 2023)
In the era of information technologies, it is demonstrated that cyber security and computer crimes are two interdependent elements that influence each other inversely proportionally in the conditions where the first one advances, the second one decreases, and vice versa. Many times, the persons responsible do not draw due attention to the need to strengthen cyber security, and law enforcement bodies, through the lens of the existing criminal framework, can hardly cope with cyber-attacks, information warfare, the massive influence on electoral processes, the manipulation of public opinion, from platforms and well-organized fake profiles and run from specific interest groups and command centers, equipped with the latest computer technologies and trained specialists. These would be just a few dangers that threaten the democratic processes in society, including the security of the state with the risk of deviating from the path proposed for the Republic of Moldova - the path to the European Union.